Full mouth rehabilitation of a combined fixed and removable prosthesis: A Case report - EL BOUEIZ, Colette; ZEBOUNI, Elie (International Arab Journal of Dentistry (IAJD), 2016)
The full mouth rehabilitation seeks to restore the occlusal func- tion, in order to allow to the masticatory system to operate phy- siologically with an occlusal stability in centric relation and a well-defined anterior guidance. The esthetics in all its parameters will have to be restored, this being the patient’s chief complaint. A sequential treatment plan, where several disciplines inter-act, will be exposed in a specific order of interventions to meet the concerns expressed by the patient, especially in intermediary phases of treatment. The treatment plan will include a periodontal initial preparation, extraction of unfavorable teeth with a period of fixed temporiza- tion at the lower jaw and a temporary removable appliance at the upper jaw. The final prosthesis will be as follow: fixed prosthesis on all teeth at the mandible and a removable prosthesis (overdenture type) at the maxilla.